Kewartawanan Advokasi: Elemen Advokasi Utusan Pengguna Sebagai Alat Sokongan Rakyat (Advocacy Journalism: Advocacy Elements in Utusan Pengguna As A Citizen Support Tool) - Ibrahim, Zaim Aiman; Nayan, Shahreen Mat (Universiti Kebangsaan Malaysia Press, 2018)
Journalism’s extensive role provides huge benefits to the community and social system. In the Malaysian context, journalism mostly focuses on issues related to politics, sports, economy and business. However, both traditional and new media outlets are less likely to give attention to issues related to consumerism. Advocacy journalism in Malaysia is still in its infancy. Advocacy journalism refers to how journalists not only report a problem, but also serves to mediate in resolving an issue (Dixit, 2010). Various issues of consumer, environmental, and social problems faced by society has been under-reported by the media. This article will clarify how journalists contribute to social change in the Malaysian context. The issue will be explored by focusing on advocacy elements in journalism that have been proven to be effective. Further, to analyze the issue, Utusan Pengguna was chosen for this case study. This article specifically discusses how advocacy elements have been applied to solve environmental and consumer issues. A qualitative approach was used to interview four individuals who are well-versed in the field of journalism. It is fair to state that, the advocacy approach adopted by Utusan Pengguna journalists have made a positive impact on the society. The newspaper provides a platform for marginalized groups to voice their concerns. In summary, investigative reporting contributes to social change.